1994
DOI: 10.1161/01.str.25.2.309
|View full text |Cite
|
Sign up to set email alerts
|

Relation of cerebral blood flow to motor and cognitive functions in chronic stroke patients.

Abstract: The aim of this study was to examine the levels of cerebral blood flow in relation to motor and cognitive functions in 300 chronic unilateral stroke patients (age, 64 +/- 12 years; mean +/- SD). Cerebral blood flow was measured by the 133Xe inhalation method, adjusted for age, sex, and PCO2 level. Motor function was scored according to Brunnstrom hemiplegic staging and cognitive function according to the Hasegawa dementia rating scale tested in Japanese. Asymmetries of blood flow between af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 67 publications
2
17
0
Order By: Relevance
“…In addition, we found that an increase in CBF correlated with reduction in locomotion during the light phase. These observations were consistent with those of previous studies, which showed that increased CBF is associated with improved neurological recovery [63][64][65]. However, the mechanism of angiogenesis-mediated functional recovery has remained unclear.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we found that an increase in CBF correlated with reduction in locomotion during the light phase. These observations were consistent with those of previous studies, which showed that increased CBF is associated with improved neurological recovery [63][64][65]. However, the mechanism of angiogenesis-mediated functional recovery has remained unclear.…”
Section: Discussionsupporting
confidence: 93%
“…It is possible that the widespread and lesionspecific metabolic changes after cerebral ischemia as observed in our patients were responsible for a residual deficit, as has been reported for patients with hemiparesis, neglect, and aphasia. [2][3][4]43,44 However, a consequential relationship between the observed widespread and remote changes in cerebral activity and functional recovery has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the widespread and lesionspecific metabolic changes after cerebral ischemia as observed in our patients were responsible for a residual deficit, as has been reported for patients with hemiparesis, neglect, and aphasia. [2][3][4]43,44 However, a consequential relationship between the observed widespread and remote changes in cerebral activity and functional recovery has not been demonstrated.In this study we show by means of a PCA that brain areas participating in a network related to recovery from brain infarction in the middle cerebral artery territory were also shared by another network that was affected by the stroke lesion. Specifically, the lesion-affected PC1 shared the same core areas as PC3 (Table 1).…”
mentioning
confidence: 99%
“…Neuroimaging indicates that GVS increases blood flow [8], and electrical power spectra [9] in those temporalparietal and frontal regions of brain typically damaged in neglect. Such increases may be important for subsequent cognitive restoration and behavioural improvement [10]. At the psychological level, Karnath [11] has proposed that the central transformation that converts sensory input co-ordinates into an egocentric, bodycentered co-ordinate system is systematically skewed in neglect, resulting in a horizontal deviation of the spatial reference frame to the ipsilesional side.…”
Section: Introductionmentioning
confidence: 99%